Non-targeted metabolomics reveals fatty acid and associated pathways driving resistance to whitefly and tomato leafminer in wild tomato accessions - Sunil Kumaraswamy; Kalenahalli Yogendra; Paola Sotelo-Cardona; Aparna Shivanna; Sanivarapu Hemalatha; Muthugounder Mohan; Ramasamy Srinivasan (Scientific Reports)
Abstract Wild tomato species exhibit natural insect resistance, yet the specific secondary metabolites and underlying mechanisms governing the resistance remain unclear. Moreover, defense expression dynamically adapts to insect herbivory, causing significant metabolic changes and species-specific secondary metabolite accumulation. The present study aims to identify the resistance-related metabolites in wild tomato accessions that influence the defense mechanism against whitefly (Bemisia tabaci Asia II 7) and leafminer (Phthorimaea absoluta). In this study, LC-HRMS-based non-targeted metabolomics of resistant wild (Solanum cheesmaniae and Solanum galapagense) and susceptible cultivated (Solanum lycopersicum) accessions following 6- and 12-h post-infestation (hpi) by B. tabaci Asia II 7 and P. absoluta revealed distinct sets of resistance-related constitutive (RRC) and induced (RRI) metabolites. The key resistance-related metabolites were those involved in the fatty acid and associated biosynthesis pathways (e.g., triacontane, di-heptanoic acid, dodecanoic acid, undecanoic acid, N-hexadecanoic acid, pentacosane, monogalactosyldiacylglycerols, sphinganine, and 12-hydroxyjasmonic acid), which are recognized for their direct or indirect role in mediating plant defense against insects. Additionally, the differential accumulation of metabolites was evident through partial least squares-discriminant analysis (PLS-DA), highlighting differences in metabolite profiles between resistant and susceptible accessions at 6 and 12 hpi of B. tabaci and P. absoluta. Volcano plot analysis revealed a higher number of significantly upregulated metabolites in wild accessions following herbivory. Moreover, wild tomato accessions responded uniquely to B. tabaci and P. absoluta, highlighting species-specific metabolic responses of tomato accessions to the two feeding guilds. This study uncovered biochemical mechanisms governing resistance in wild tomato accessions, elucidated the influence of dual herbivory on the plant metabolome, and offered well-characterized parent materials and candidate metabolites for breeding insect-resistant varieties.